3D finite element analysis of heat transfer efficiency in double wall infant incubator - Wongkamhang, A.; Phasukkit, P.; Airphaiboon, S.; Pintavirooj, C.; Thongpance, N.; Sanpanich, A. (My University, 2012)
This paper presents a study of heat transfer efficiency in double wall infant incubator by using 3D finite element method. Double wall infant incubator was modeled by using general CAD program then FEM analysis was implemented based on heat transfer and fluid dynamic principle. Real temperature measurement also performed to validate our simulation by using a general infant incubator and an infant incubator analyzer. Real experimental data at each 4 monitoring points and simulation data provide a small difference in temperature. In the future work, infant model should be included into our incubator in order to estimate a heat source effect from newborn baby. ©2012 IEEE.
Keywords: 3D finite element analysis; Double wall infant incubator; Heat transfer